Proceedings of the Annual Civic Education Conference (ACEC 2018) 2018
DOI: 10.2991/acec-18.2018.126
|View full text |Cite
|
Sign up to set email alerts
|

Development of Values Transformation Modes of Local Wisdom of Baduy Culture to Form Student Character through Civic Learning in Elementary School: A study of Attitude of Elementary School Students in Kasepuhan Citorek Adat Area, Lebak Regency, Banten Province

Abstract: The development of science and technology has influenced people's mindset and orientation at all levels. The rapid development of information technology also influence the behavior of some people, including the character of the students. Having a good character means having the ability to communicate and behave in a manner consistent with the values prevailing in society. The superior value of local culture as a regional potential needs to be passed on to the next generation. Therefore, the transformation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Having good character means having the ability to communicate and behave following the values prevailing in the society. Social participation is one of the forerunners in the process of a nation's participation in a country (Elan et al, 2018). The results of a study in three Junior High Schools in Sweden have concluded that action groups represent an arena for the individual and collective performance, where individual and collective ideas can be reflected (Rönnlund 2010).…”
Section: Social Participationmentioning
confidence: 99%
“…Having good character means having the ability to communicate and behave following the values prevailing in the society. Social participation is one of the forerunners in the process of a nation's participation in a country (Elan et al, 2018). The results of a study in three Junior High Schools in Sweden have concluded that action groups represent an arena for the individual and collective performance, where individual and collective ideas can be reflected (Rönnlund 2010).…”
Section: Social Participationmentioning
confidence: 99%
“…Komalasari, Saripudin [13] stated that values are not only captured and taught, but a learning process is needed to capture, internalize, and standardize values as an inherent part of a person. Elan, Sapriya, Abdulkarim [14] stated that the transformation of the value of local wisdom through the learning process needs to be well designed to strengthen students' good character. Based on the notions previously described the positive impact of the siri' na pacce value on human behavior and the effort of fostering students' good character through culture-based learning, the researchers deduce the need to develop a learning model based on the value of siri' na pacce to maintain the students' good character.…”
Section: Introductionmentioning
confidence: 99%
“…All components of the nation need to play an active role in developing the nation's culture and character (Kementerian PPN/Bappenas, 2019). Noble values coming from local wisdom, as part of Indonesia's cultural wealth, need to be preserved and passed on to the younger generation (Elan, Sapriya, & Abdulkarim, 2018;Azis, Saleh, & Suriani, 2020). Teachers, as the main education actors in schools, need to play an active role in understanding and passing on local culture, including local tribal wisdom such as pacce and reso values, to shape student attitudes.…”
Section: Introductionmentioning
confidence: 99%